2015
DOI: 10.1007/s11002-015-9369-7
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of opinion leadership in customer networks: self-reports and degree centrality

Abstract: In this paper, we assess two alternative indicators of opinion leadership, selfreported opinion leadership and degree centrality, on the same dataset. We also investigate the interaction effect of these two indicators and the social network environment on opinion leadership. We use social network and survey data from the mobile telecom industry to analyze opinion leadership in smartphone adoption. We find that degree centrality indicates opinion leadership, but that self-reported opinion leadership indicates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…Network centrality is often equated with power and influence in groups (Friedkin, 2001); central consumers thus tend to be depicted as prominent influencers of more peripheral consumers (Lee et al, 2010;Risselada et al, 2015). Focusing on the context of shared consumption, the current findings suggest that this social asymmetry actually is a double-edged sword: The difference in centrality exerts some conformity pressure on the most peripheral consumer in the dyad but also may result in a boomerang effect, through reactance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Network centrality is often equated with power and influence in groups (Friedkin, 2001); central consumers thus tend to be depicted as prominent influencers of more peripheral consumers (Lee et al, 2010;Risselada et al, 2015). Focusing on the context of shared consumption, the current findings suggest that this social asymmetry actually is a double-edged sword: The difference in centrality exerts some conformity pressure on the most peripheral consumer in the dyad but also may result in a boomerang effect, through reactance.…”
Section: Discussionmentioning
confidence: 67%
“…High network centrality affects a variety of marketing outcomes, including new product adoption (Katona, Zubcsek, & Sarvary, 2011;Kim & Park, 2011), product-related information-seeking behavior (Lee, 2014), and shopping behavior (Gentina & Bonsu, 2013). In a similar vein, centrality appears correlated with opinion leadership (Gentina, Butori, & Heath, 2014;Lee et al, 2010;Risselada, Verhoef, & Bijmolt, 2015). Central consumers are influential, first, because the number of others they reach in their daily social interactions is greater than the number reached by more peripheral consumers.…”
Section: Network Centrality and Consumer-to-consumer Influencementioning
confidence: 96%
“…Previous literature has identified key players, similar to perceived opinion leaders, who affect new product adoption according to their structural position in their networks or the outcome of their positions (e.g. central actors/players, hubs) (Goldenberg et al, 2009;Iyengar et al, 2011;Risselada et al, 2016). Social media opinion leaders are individuals who are extensively involved in relationships and communication with other actors (Wasserman and Faust, 1996) and are exposed to innovations earlier than others in their networks (Goldenberg et al, 2009).…”
Section: Perceived Opinion Leadership Social Media Opinion Leadership and New Product Adoptionmentioning
confidence: 99%
“…Then, the discovery of opinion leaders associates sentiment analysis to candidates with the sentiment with the actual price movement trend [23]. Risselada et al find that degree centrality indicates opinion leadership, but that self-reported opinion leadership indicates opinion leadership only under the right social circumstances [24]. Rocha et al present a preliminary evaluation about a combined analysis of Sentiment Analysis and Influential Users Detection and propose a methodology to quantify factors in real domains that may affect such analysis, as well as the potential benefits of combining Sentiment Analysis Methods with Influential Users Detectionones [25].…”
Section: B Opinion Leader Rolementioning
confidence: 99%